Text, Palace, Tourism: Exploring Literary Tourism in a Classical Javanese Literature, Wedhatama by King Mangkunegara IV, Central Java, Indonesia - Esti Ismawati; Warsito Warsito; Kun Andyan Anindita (Javanologi: International Journal of Javanese Studies, 2023)
Wedhatama, which was published in 1680 at the Surakarta Palace, is still popular today because it contains the concept of tri ugering ngaurip (three philosophies of life), namely arta, (about financial independence), wirya (about honor), and tri winasis (about how to gain intelligence). This study aims to critically examine how Wedhatama, a classic Javanese literary book by King Mangkunegara IV of the Surakarta Palace, contains philosophical values of life and how Javanese culture in the palace can become an interesting literary tourism object. The problem that will be answered in this paper is, "Are Wedhatama and the Mangkunegaran Palace of Surakarta worthy of being literary tourism destinations in Indonesia and even the world? This study will answer how the response of "Pura Mangkunegaran" regarding this matter. In-depth interviews with palace relatives, namely RM Darajadi Gandadipraja about Wedhatama and interviews with tourists who came to ensure that Wedhatama, the Mangkunegaran Palace, and their culture are very interesting to visit. It can be concluded that Wedhatama, the Mangkunegaran Surakarta palace, the tomb of King Mangkunegara IV, and their relics, are worthy of being literary tourism destinations, both for the Indonesian public and the world.